Bacillus spp. Contamination: A Novel Risk Originated From Animal Feed to Human Food Chains in South-Eastern Bangladesh - Haque, Md Atiqul; Wang, Fei; Chen, Yi; Hossen, Foysal; Islam, Md Aminul; Hossain, Md Amzad; Siddique, Naila; He, Cheng; Ahmed, Firoz (Frontiers in Microbiology, 2022)
The current study provides information on Bacillus spp. contamination along with present status in commercially available poultry and animal feeds as well as animal-derived products in Bangladesh. The research has been conducted to determine if animal feed and its components are a source of Bacillus spp. contamination in feed and food chain. Out of 180 different feeds, milk, egg, and human stool samples, 218 Bacillus spp. were isolated and identified by cultural morphology, microscopic, biochemical, and molecular characteristics where B. cereus, B. subtilis, B. amyloliquefaciens, B. licheniformis, B. thuringiensis, B. megaterium, and B. coagulans accounted for 51, 22, 9.1, 5.9, 5, 3.6, and 2.2%, respectively. Regarding the enumeration of total viable count and total Bacillus count, correspondingly 67 and 39% samples were found to be contaminated with above 10,000 CFU/g, while highest contamination was 85 and 75% in broiler feed, respectively. The total number of bacteria above the regulatory limits in commercially available feeds indicates a poor compliance with regulation and abuse administration in the Bangladeshi market. Moreover, a hospital-based survey showed that food-borne Bacillus spp. contributed to 4.5% human diarrhea cases and 25% food contamination associated with vegetables, rice, RTE food, milk, and egg, accounting for 46, 34, 14, 4, and 2%, respectively. B. cereus was the dominant isolate correspondingly accounting for 56 and 51% egg and milk contamination followed by B. amyloliquefaciens (32%) and B. thuringiensis (12%) in egg and B. subtilis (25%), B. amyloliquefaciens (12%), B. thuringiensis (6.4%), and B. coagulans (3.2%) in milk, respectively. Toxin gene profiling of Bacillus spp. revealed that B. cereus constituted a principal part of virulence, while B. thuringiensis, B. licheniformis, B. megaterium, B. coagulans, and B. subtilis showed genetic diversity and B. amyloliquefaciens had not carried any toxin gene. Detection rate of enterotoxin genes (nheA, nheB, nheC, cytK, hblA, hblC, hblD, and entFM) showed that 55% isolates carried nheABC genes, 80% entFM, and 71% cytK, whereas only 33% of the isolates contained hblACD gene clusters. These virulence genes were posing a threat to human health due to spread across the food and feed chain. Finally, our findings support the hypothesis that B. cereus might contribute to clinical diarrhea, gizzard erosion, and lung infection in duck and poultry, and that it contaminates animal-derived foods resulting in toxicity and antibacterial resistance to humans. Therefore, maximal tolerance limits of Bacillus spp. and their potential risks to the animal industry are urgently needed to clarify. Moreover, Bacillus spp.–induced toxin residual must be altered for human health via food chain transmission.